The role of guided educational games in developing motor skills in preschool children aged 4-6 years - Ben Misra, Abderrahman (sports creativity, 2025)
This study aims to identify the role of guided educational games in developing motor skills among preschool children aged 4-6 years. To achieve the objectives of this study, the experimental method was used with two groups: an experimental group and a control group, comprising a sample of 40 children. Statistical analysis was performed using percentages, arithmetic means, and t-tests. The results of this study indicated an improvement in the level of motor skills attributed to the role of guided educational games, with statistically significant differences between the two groups across all variables, favoring the experimental group.